2001
DOI: 10.1007/s001040170036
|View full text |Cite
|
Sign up to set email alerts
|

Die „frozen shoulder“Arthroskopische, histologische und elektronenmikroskopische Untersuchungen

Abstract: In stage of the primary frozen shoulder exclusive fibrosis of the joint capsule was found. Electronmicroscopic twists of collagen fibrills were marked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 9 publications
1
2
0
2
Order By: Relevance
“…Several authors have reported that stiff shoulder in diabetics had a poorer outcome 616182429. Our study also showed that patients with shoulder stiffness and diabetes mellitus had a relatively poor outcome and unsatisfactory results.…”
Section: Discussionsupporting
confidence: 60%
“…Several authors have reported that stiff shoulder in diabetics had a poorer outcome 616182429. Our study also showed that patients with shoulder stiffness and diabetes mellitus had a relatively poor outcome and unsatisfactory results.…”
Section: Discussionsupporting
confidence: 60%
“…Some more recent arthroscopic investigations of frozen shoulder patients report no distinct intraarticular adhesions of this type [ 6 - 9 ], and the role of such adhesions is unclear. The finding of contractions of the joint capsule is supported though, as the studies describe a marked reduction in joint volume [ 6 - 9 ] due to contraction of collagenous tissue surrounding the joint [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mehrere Arbeiten fanden sich in den Literaturlisten der in Medline gefundenen Artikel (siehe Begrenzungen der Studie). Analysiert wurden 6 historische experimentelle kontrollierte Tierstudien [20,24,26,27,31,35], 2 beschreibende Studien am Menschen [15,22] [26] sowie Ushida und Willis [46], die auch die Ruhigstellung nach Gelenkfrakturen beobachteten. Die für die einzelnen Fragestellungen relevanten Ergebnisse werden nachfolgend dargestellt.…”
Section: Ergebnisseunclassified
“…Allgemein ist bei der Interpretation der Studien zu beachten, dass es sich bis auf die beschreibenden Studien am Menschen von Enneking und Horowitz [15] und Kilian et al [22] um Tieruntersuchungen handelt. Die Übertragbarkeit der Ergebnisse auf den Menschen bleibt unklar.…”
Section: Diskussionunclassified